Ascertaining Leadership Styles Of Defence Funded Schools (International Journal of Scientific Research and Management (IJSRM), 2016)
Educational Leadership is identified as an important factor for quality education. Successful leadership is notthe result of simply obtaining a position, but rather possessing the knowledge and understanding of successful leadership skills along with the personal ability to effectively implement those skills. Hence, School Principals need impressive skills to provide effective leadership in diverse school environments. Throughout the world, education policy makers are constantly looking for ways to prepare school leaders to deal with the complex challenges facing public education in the 21st century. Research has demonstrated a clear correlation between effective school leadership and student achievement. The purpose of the study is to explore the leadership styles adopted by Principals of Defence funded Schools and highlight research issues in relation to overall performance and Students achievementas conceptualized by Bolman and Deal’s Four-Frame Model of Leadership (1991).